THE EFFECT OF LABOR FORCE PARTICIPATION RATE, NUMBER OF SMOKERS AND GDP GROWTH RATE ON POVERTY IN JAVA ISLAND - Widyawati, Retno Febriyastuti; Yusfi, Reikha Habibah (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to analyze the effect of TPAK, smoking behaviour, and GRDP growth rate on poverty in the Regency/City of 4 Provinces in Java Island in 2023. This research is quantitative, using secondary data and the cross-section method. The sampling method used is Purposive Sampling. The results of this study indicate that the TPAK variable affects poverty in the Regency/City of 4 Provinces on the island of Java. In comparison, the smoking behaviour variable and the GRDP growth rate do not affect poverty in the Regency/City of 4 Provinces in Java. Simultaneously, the TPAK variable, smoking behaviour, and GRDP growth rate together affect the poverty of the Regency/City of 4 Provinces on the island of Java in 2023